The dietary habits and life satisfaction according to the food groups consumed by young people - Türkmen, Hülya; Karaca Sivrikaya, Sibel (Progress in Nutrition, 2021)
Aim: To determine the relationship between the food groups consumed by students and the dietary habits and lifesatisfaction.Methods: The cross-sectional study was carried out with 811 students studying in Balıkesir University, Faculty of Health Sciences in January 2018 in Turkey. In this study, Personal Information Form, Survey of Eating Habits and Satisfaction with lifeScale that included the socio-demographic characteristics and the frequency of food consumption of the students were used. Kolmogorov Simirnov test, mean, standard deviation, number, percentage, Mann Whitney U test, Kruskal Wallis test, Spearman correlation and multiple linear regression analysis were used in the evaluation of the data.Results: Satisfaction with lifescores of students who often consume grains, fruits, meat and its derivatives were found to be high.It was determined that as self-perception against being overweight and eating habits scores increase, lifesatisfaction decreases in students. Prejudice score against being overweight was found to be high in students studying nursing care, whose BMI is normal and who rarely consume vegetable. The positive and negative thought scores caused by being overweight were found to be high in overweight / obese students who often consume dairy product and legume. The self-perception score against being overweight was found to be high in students who are obese and often consume dairy products. Eating habits score was found to be high in weak students who rarely consume dairy products and fruit (P